Kepemimpinan Berbasis Pelanggan dalam Blue Ocean Strategy : Fokus Pada Kepuasan Pelanggan Sebagai Keunggulan Kompetitif - Rahmat Hidayat; Muhammad Falih A.F; Marschanda Dian Estika; Narendra Dwi Siswanto; Mochammad Isa Anshor (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This research analyzes the role of customer-based leadership in implementation of Blue Ocean Strategy (BOS) to create competitive advantage through customer satisfaction. Through customer satisfaction. Using a qualitative descriptive method with literature study, this research highlights how a customer-oriented leader can identify new needs and customer-oriented leaders can identify new needs and create value innovation. Research results showed that customer-driven leadership significantly contributes to to the success of BOS by increasing customer loyalty and unique unique experiences. The case studies of Tesla and Starbucks prove that this this approach can create new markets with less competition. Conclusion, customer-centered leadership in BOS not only increases customer satisfaction, but also strengthens the company's long-term competitiveness. Satisfaction, but also strengthens the company's competitiveness in the long run.